2020
DOI: 10.4300/jgme-d-19-00907.1
|View full text |Cite
|
Sign up to set email alerts
|

Does Community- or University-Based Residency Sponsorship Affect Graduate Perceived Preparation or Performance?

Abstract: Background Residency training occurs in varied settings. Whether there are differences in the training received by graduates of community- or medical school–based programs has been the subject of debate. Objective This study examined the perceived preparation for practice, scope of practice, and American Board of Family Medicine (ABFM) board examination pass rates of family physicians in relation to the type of residency program (community, medical school, or partnership) in which they trained. Methods Predete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Research studies using data from the Graduate Survey have shown a large gap between practice and preparation 4 with further variation between academic-and community-based programs. 5 Other studies using the data have shown lower odds of burnout with broader scope of practice, 6 state-level variation in burnout, 7 associations between residency training and buprenorphine prescribing, 8 barriers to practicing obstetrics, 9 provision of contraceptive services and abortion care, 10,11 and participation in loan repayment programs. 12 Possible Uses and the Future With multiple years of data, residencies have the capability to identify persistent gaps in their curricula and make changes.…”
Section: Resultsmentioning
confidence: 92%
“…Research studies using data from the Graduate Survey have shown a large gap between practice and preparation 4 with further variation between academic-and community-based programs. 5 Other studies using the data have shown lower odds of burnout with broader scope of practice, 6 state-level variation in burnout, 7 associations between residency training and buprenorphine prescribing, 8 barriers to practicing obstetrics, 9 provision of contraceptive services and abortion care, 10,11 and participation in loan repayment programs. 12 Possible Uses and the Future With multiple years of data, residencies have the capability to identify persistent gaps in their curricula and make changes.…”
Section: Resultsmentioning
confidence: 92%
“…31 Conversely, a recent graduate survey indicated that graduates' actual practice scope was narrower compared with the scope they felt prepared to provide. 32 Thus, ensuring residents continue to provide a comprehensive scope of care will mean balancing training opportunities with what is needed and should be provided in the community setting. Part of comprehensiveness is focusing on quality of care for both prevention and chronic disease.…”
Section: Comprehensivenessmentioning
confidence: 99%
“…This information was used in a QI project that lead to a significant decrease in the readmission rate to an inpatient family medicine team. 10 For overall program improvement to truly occur, the patient care, scholarship, and community activities of graduates need to be assessed and used in program improvement activities. Currently programs are only required to monitor board pass and certification rates of graduates.…”
Section: Special Articlesmentioning
confidence: 99%
“…12 This tool has been used in the literature to further assess family medicine residency training. 10 The discipline needs to go beyond this graduate survey and include patient quality of care measures, patient satisfaction surveys, and community activities of graduates.…”
Section: Going Forward-recommendations For the Future Of Residency Trainingmentioning
confidence: 99%